2008
DOI: 10.1128/aem.01512-07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Turning and Environmental Contamination on the Dynamics of Populations of Lactic Acid and Acetic Acid Bacteria Involved in Spontaneous Cocoa Bean Heap Fermentation in Ghana

Abstract: The influence of turning and environmental contamination on six spontaneous cocoa bean heap fermentations performed in Ghana was studied through a multiphasic approach, encompassing both microbiological (culture-dependent and culture-independent techniques) and metabolite target analyses. A sensory analysis of chocolate made from the fermented, dried beans was performed as well. Only four clusters were found among the isolates of acetic acid bacteria (AAB) identified: Acetobacter pasteurianus, Acetobacter ghan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(172 citation statements)
references
References 34 publications
10
150
0
7
Order By: Relevance
“…The closest relatives of the sequenced fragments were determined via GenBank searches for sequences with over 98 % similarity: A = S. cerevisiae; B = P. kluyveri; C = Candida sp. ; D = H. guilliermondii; E = H. uvarum; F = Theobroma cacao fermented grains, and, consequently, the final product (Camu et al 2008). According to previous research, yeasts are essential for the development of chocolate flavor and their inoculation may accelerate and control the fermentation process (Batista et al 2015;Ho et al 2014;Ramos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The closest relatives of the sequenced fragments were determined via GenBank searches for sequences with over 98 % similarity: A = S. cerevisiae; B = P. kluyveri; C = Candida sp. ; D = H. guilliermondii; E = H. uvarum; F = Theobroma cacao fermented grains, and, consequently, the final product (Camu et al 2008). According to previous research, yeasts are essential for the development of chocolate flavor and their inoculation may accelerate and control the fermentation process (Batista et al 2015;Ho et al 2014;Ramos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Processing of cocoa on the farms begins with the opening of the fruit (pods) in the field under the trees, where the seeds are separated from the husks. The seeds are then fermented in wooden boxes and sun-dried, to be later processed in the factory (Forsyth and Quesnel, 1957;Kalvatchev et al, 1998;Camu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of flora bacterial at the start of fermentation was similar to that observed in many countries [3,38]. According to some authors [2,39,40 which colonized cocoa fermenting mass come from the cocoa pod surface mainly, hands of workers, knives, unwashed baskets used for transport of seeds, and dried mucilage left on et al: Cocoa Fermentation from Agnéby-Tiassa: Biochemical Study of Microflora According to a report [2], observed during fermentation was associated to intense metabolic activity of process, reaching sometimes about 50°C at the end of the process. Overall, ed in cocoa fermentation provided an ecosystem that selected for the successional growth of various species of yeasts, lactic acid bacteria, acetic and pH during cocoa fermentation.…”
Section: Figure 1 Evolution Of Temperature and Ph During Cocoa Fermementioning
confidence: 49%